2021
DOI: 10.3390/ijerph182111289
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Absolute Neutrophil Counts in Patient on Clozapine Infected with COVID-19

Abstract: Despite its severe adverse effects, such as agranulocytosis, clozapine is the primary treatment for treatment-resistant schizophrenia. The established clozapine monitoring system has contributed to reducing agranulocytosis incidence and mortality rates. However, the pandemic coronavirus disease 2019 (COVID-19) has caused changes in the monitoring system. This review aimed to assess the current evidence on the neutrophil changes in the patient on clozapine treatment and infected with COVID-19. Individual cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…Blood cell count and clozapine plasma concentration should be measured before and after the vaccination. 40…”
Section: Discussionmentioning
confidence: 99%
“…Blood cell count and clozapine plasma concentration should be measured before and after the vaccination. 40…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Gee and Taylor (2021) demonstrated that COVID-19 infection leads to a temporary ANC reduction in patients treated with clozapine. Subsequent case reports corroborated this finding (Bonaccorso et al ., 2021; Hata et al ., 2021; Ramli et al ., 2021; Moga et al ., 2022b). Nevertheless, as there were no comparison groups in these studies, it was difficult to ascertain whether the changes were non-specific findings in patients with SMIs (De Hert et al ., 2021) or the outcome of a unique interaction of clozapine with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, an unexpected drop in the neutrophil count is frequently observed in clozapine-treated COVID-19 patients (Gee and Taylor, 2020, 2021). Clinicians worry that this response signifies a decompensating hematological system (Bonaccorso et al ., 2021; Ramli et al ., 2021; Moga et al ., 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Sama dawka nie wpływała na ryzyko ciężkiej neutropenii [27,28]. Innym czynnikiem ryzyka był krótki czas leczenia, ponieważ spadek ANC był większy u pacjentów na początku leczenia [29] niż u pacjentów długotrwale stosujących klozapinę. Jednakże odnotowano również pewne wyjątki -jeden przypadek ciężkiej agranulocytozy wystąpił u pacjenta, który rozpoczął leczenie klozapiną w 2007 roku [30].…”
Section: Dyskusja I Wnioskiunclassified